Agroindustrial Wastes as Alternative for Lipase Production by Candida viswanathii under Solid-State Cultivation: Purification, Biochemical Properties, and Its Potential for Poultry Fat Hydrolysis - De Almeida, Alex Fernando; Dias, Kleydiane Braga; Da Silva, Ana Carolina Cerri [UNESP]; Terrasan, Cï¿½sar Rafael Fanchini [UNESP]; Tauk-Tornisielo, Sï¿½mia Maria [UNESP]; Carmona, Eleonora Cano [UNESP] (Hindawi, 2016)
The aims of this work were to establish improved conditions for lipase production by Candida viswanathii using agroindustrial wastes in solid-state cultivation and to purify and evaluate the application of this enzyme for poultry fat hydrolysis. Mixed wheat bran plus spent barley grain (1: 1, w/w) supplemented with 25.0% (w/w) olive oil increased the lipase production to 322.4%, compared to the initial conditions. When olive oil was replaced by poultry fat, the highest lipase production found at 40% (w/w) was 31.43 U/gds. By selecting, yeast extract supplementation (3.5%, w/w), cultivation temperature (30ï¿½C), and substrate moisture (40%, w/v), lipase production reached 157.33 U/gds. Lipase was purified by hydrophobic interaction chromatography, presenting a molecular weight of 18.5 kDa as determined by SDS-PAGE. The crude and purified enzyme showed optimum activity at pH 5.0 and 50ï¿½C and at pH 5.5 and 45ï¿½C, respectively. The estimated half-life at 50ï¿½C was of 23.5 h for crude lipase and 6.7 h at 40ï¿½C for purified lipase. Lipase presented high activity and stability in many organic solvents. Poultry fat hydrolysis was maximum at pH 4.0, reaching initial hydrolysis rate of 33.17 mmol/L/min. Thus, C. viswanathii lipase can be successfully produced by an economic and sustainable process and advantageously applied for poultry fat hydrolysis without an additional acidification step to recover the released fatty acids.